The M(r) 80,000 common forms of neurophysin and vasopressin from bovine neurohypophysis have corticotropin- and β-endorphin-like sequences and liberate by proteolysis biologically active corticotropin - Lauber, Marc (1981)
We have tested the hypothesis that the high M(r) forms common to both neurophysin and vasopressin detected in bovine neurohypophysis extracts (Nicolas, P., Camier, M., Lauber, M., Masse, M.-J. O., Möhring, J. & Cohen, P. (1980) Proc. Natl. Acad. Sci. USA 77, 2587-2591) might also contain the sequences of other known neuropeptides. The following evidence indicates that corticotropin- and β-endorphin-like sequences are associated with similar high M(r) forms and are included in these M(r) 80,000 molecules. During the fractionation steps of high M(r) material, both corticotropin and β-endorphin immunoreactive species were found to coelute with the neurophysin and vasopressin ones, either under M(r) 140,000 (in 0.1 M formic acid) or M(r) 70,000-80,000 (in 6 M guanidine) elution volumes. Corticotropin immunoreactivity was found to cofocus at pIs 6.05 and 5.8 with the M(r) 80,000 neurophysin-containing species. This material was submitted to affinity chromatography on purified anti-neurophysin antibodies covalently attached to Sepharose 4B. Both the corticotropin and β-endorphin immunoreactivities, together with the neurophysin and vasopressin immunoreactivities, were retained on the immunoadsorbent and codesorbed by either a drastic pH change or by selective displacement with an excess of neurophysin. Comparison of the tryptic-digest maps of either the M(r) 68,000 fragment immunoprecipitated by anti-corticotropin antibodies or the M(r) 68,000 fragment released after precipitation of the M(r) 80,000 species by anti-neurophysin antibodies indicated large sequence homologies. Exposure of either the M(r) 80,000 or 68,000 components to mild proteolytic activities resulted in the formation of lower-size fragments. The resulting corticotropin-like immunoreactive material, recovered under the elution volume of standard (125)I-labeled corticotropin-(1-24), was tested for its ability to activate glucocorticoid biogenesis by the amphibian interrenal tissue (adrenal) in perifusion. It was found to exhibit a noticeable activity qualitatively undistinguishable from the one of the reference human corticotropin-(1-39). The name neurohypophyseal “coenophorin” (from the Greek word for common) is proposed for this class of M(r) 80,000 polypeptides that might represent the common precursor store-house for a set of neuropeptides produced in the hypothalamo-neurohypophyseal tract.